Determination of advantame in sauce products by ultrasonic extraction-high performance liquid chromatography and its uncertainty analysis - HUANG Huimin, LIU Ning, DUAN Hu, YANG Guang (Zhongguo niangzao)
The ultrasonic extraction-high performance liquid chromatography (HPLC) method for the detection of advantame in sauce products was established by optimizing instrument detection conditions. A mathematical model was established to analyze the uncertainties introduced by the standard solution, standard curve fitting, sample pretreatment, HPLC, and measurement repeatability. The results showed that after ultrasonic extraction, the sauce products sample was centrifuged, and separated on a C18 column (150 mm×4.6 mm, 5 μm) (column temperature 30 ℃) with acetonitrile-water as mobile phase for gradient elution. The excitation wavelength was 232 nm and the emission wavelength was 313 nm. Under these detection conditions, the retention time of advantame was 7.069 min, the linear regression equation was y =1.64e+ 005x+2.74e+002 with good linear relationship in the concentration range of 0.05-5 μg/ml, the correlation coefficient (R2) was 0.999 8, the limit of detection was 0.25 mg/kg, the limit of quantitation was 0.625 mg/kg, the recovery rate was 91.2%-98.5%, and the relative standard deviation (RSD) of the precision test results was 1.09%-2.48%. The method had the advantages of simple extraction, less pollution, short time, high sensitivity, accurate and stable results, which could be applied to the determination of advantame in sauce products. The main source of uncertainty in the method was the standard curve fitting (0.029 8), which was a key control point in the detection process.